The impact of educational attainment on the transition from nonrenewable to renewable energy use in Nigeria - Saibu, Olufemi Muibi; Olagunju, Opeyemi Balikis (Energy Economics Letters, 2023)
This paper examines the role of education in promoting renewable energy in Nigeria based on data from 1990 to 2021 using FMOLS second-generation cointegration to estimate two proxies of renewable energy. It also examines how economic growth spurs education as a driver of energy transition and tests the energy mix hypothesis in Nigeria by employing real economic growth and the import of fossil fuels as controllable variables in a model with four education indicators. The results showed that education is vital to Nigeria’s renewable energy goals. In contrast to existing studies, the study established that all types of education encourage the move from nonrenewable to renewable energy consumption in Nigeria. However, technical and university education are the most crucial in Nigeria’s drive toward the adoption of renewable energy, which implies that Nigeria’s energy transformation may require more than general knowledge. The paper also established that to mitigate the influence of Nigeria’s low economic growth on its energy transition, a minimum critical level of at least 7% of the per capita income and 7%–9% of higher technical education must be attained consistently. The paper concludes that purchasing power measured by economic growth is more important than education for Nigeria’s energy shift. However, education can mitigate the detrimental effects of economic growth on energy transition potential. Therefore, policy to promote energy transition with technical educational development and economic empowerment is needed to achieve Nigeria’s energy transformation goal.